Modelo framework para avaliação pulmonar em pacientes não colaborativos - Costa, Kamila Nóbrega de França (2020)
Introduction: Health care must move towards an increasing recognition of changes in the selection of its clinical evaluation models, observing an increasing incorporation of health technologies that demonstrate the effectiveness and potential of clinical responses in a patient-centered model, mainly used previously as non-collaborative. In lung health, tests and technologies can play an essential role from early diagnosis to the treatment of your lung conditions. Objective: To create a proposal for a structure with clinical support recommendations for health technologies in efficient use in the assessment of lung function in non-collaborating patients. Methodology: It is a secondary study, of the type integrative literature review, carried out from January to April 2019. And, at the same time, it captures a construction of clinical pulmonary assessment tests for non collaborative patients based on the structure model addressed by Guyatt et al. (1986) and economic statistics. Expected impacts and results: It was possible to build clinical recommendations for pulmonary assessment for non-collaborative patients based on the structure model adopted in the north of the country and to facilitate clinical clinics in the respiratory conditions of non-collaborative patients, bringing therapeutic innovation to this type audience.